The Application of Basic Football Learning Models by Using Applications to Increase Learning Outcomes of Football Courses for Students of Sports Training Education in the Faculty of Sport Science, Universitas Negeri Medan 2022 - Irwansyah Siregar; Yan Indra Siregar; Ifayandi Damanik; Putra Arima (Randwick International of Social Science Journal, 2022)
This study applies the basic football learning model by using an application to improve the learning outcomes of football subjects. The research method used in this study is experimental, meaning that the research aims to find causality or causal relationships. The data obtained from the research results were analyzed quantitatively to answer the research problem formulation. The results of the study r arithmetic > r table the value of the r table is with a significance of 5% or 0.5, which is 0.138. The significance value (2-tailed) <0.05 indicates a significant increase between the initial variable and the final variable. This shows that there is a significant increase in the difference in treatment given to each variable. So it was concluded that the significance value of 0.000 < 0.05 was an increase in the application of the Basic Football Learning Model by Using Applications to Improve Learning Outcomes of Soccer Courses for Students of Sport Training Education, Faculty of Sports Science, State University of Medan in 2022. The application of basic football learning models by using applications has an impact on learning behavior and social because students become more adaptive to identify technologies that can support learningand increasing social relations. It is also improving skills related to using technology and social communication.